Infografía investigativa como herramienta comunicacional en el desarrollo cultural de los jóvenes del Recinto La Ercilia cantón Ventanas, año 2021 - Rivera Vera, Paola Rosalía (2022)
Infographics is a tool that summarizes relevant information on a topic since it is responsible for using different visual media to capture the attention of readers, it is also a technique that has achieved great prominence due to the development of technology and also thanks to the heyday of cyberjournalism in recent decades, which allowed it to obtain a place in the print, visual and digital media, because through this tool many people can be informed in a didactic way about a situation. Therefore, the main objective of this research lies in the analysis of investigative infographics as a communication tool in the cultural development of young people from the La Ercilia campus of the Ventanas canton, year 2021. The methodology used is based on the analytical, deductive and inductive technique, since these allow to deepen the subject, they are also the bases for the observation and collection of both theoretical and field information in the population of the La Ercilia enclosure of the Ventanas canton, where it was possible to recognize with 75.97% of the respondents that this communication tool can contribute significantly to the cultural development of young people.